Inhibition of IGF1-R overcomes IGFBP7-induced chemotherapy resistance in T-ALL. Issue 1 (December 2015) - Bartram, Isabelle; Erben, Ulrike; Ortiz-Tanchez, Jutta; Blunert, Katja; Schlee, Cornelia; Neumann, Martin; Heesch, Sandra; Baldus, Claudia
Abstract Background T-cell acute lymphoblastic leukemia (T-ALL) is a genetically heterogeneous disease with the need for treatment optimization. Previously, high expression of Insulin-like growth factor binding protein 7 (IGFBP7), a member of the IGF system, was identified as negative prognostic factor in adult T-ALL patients. Since aberrantIGFBP7 expression was observed in a variety of neoplasia and was relevant for prognosis in T-ALL, we investigated the functional role ofIGFBP7 in Jurkat and Molt-4 cells asin vitro models for T-ALL. Methods Jurkat and Molt-4 cells were stably transfected with an IGFBP7 over-expression vector or the empty vector as control. Proliferation of the cells was assessed by WST-1 assays and cell cycle status was measured by flow-cytometry after BrDU/7-AAD staining. The effect of IGFBP7 over-expression on sensitivity to cytostatic drugs was determined in AnnexinV/7-AAD assays. IGF1-R protein expression was measured by Western Blot and flow-cytometric analysis. IGF1-R associated gene expression profiles were generated from microarray gene expression data of 86 T-ALL patients from the Microarrays Innovations in Leukemia (MILE) multicenter study. Results IGFBP7- transfected Jurkat cells proliferated less, leading to a longer survival in a nutrient–limited environment. Both IGFBP7-transfected Jurkat and Molt-4 cells showed an arrest in the G0/G1 cell cycle phase. Furthermore, Jurkat IGFBP7-transfected cells were resistant to vincristine and asparaginase treatment. Surface expression and whole protein measurement of IGF1-R protein expression showed a reduced abundance of the receptor after IGFBP7 transfection in Jurkat cells. Interestingly, combination of the IGF1-R inhibitor NPV-AEW541 restored sensitivity to vincristine in IGFBP7-transfected cells. Additionally, IGF1-R associated GEP revealed an up-regulation of important drivers of T-ALL pathogenesis and regulators of chemo-resistance and apoptosis such as NOTCH1, BCL-2, PRKCI, and TP53. Conclusion This study revealed a proliferation inhibiting effect of IGFBP7 by G0/G1 arrest and a drug resistance-inducing effect of IGFBP7 against vincristine and asparaginase in T-ALL. These results provide a model for the previously observed association between highIGFBP7 expression and chemotherapy failure in T-ALL patients. Since the resistance against vincristine was abolished by IGF1-R inhibition, IGFBP7 could serve as biomarker for patients who may benefit from therapies including IGF1-R inhibitors in combination with chemotherapy.